2017
DOI: 10.1016/j.jcmgh.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor (HIF) Hydroxylases as Regulators of Intestinal Epithelial Barrier Function

Abstract: Human health is dependent on the ability of the body to extract nutrients, fluids, and oxygen from the external environment while at the same time maintaining a state of internal sterility. Therefore, the cell layers that cover the surface areas of the body such as the lung, skin, and gastrointestinal mucosa provide vital semipermeable barriers that allow the transport of essential nutrients, fluid, and waste products, while at the same time keeping the internal compartments free of microbial organisms. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 171 publications
1
52
0
Order By: Relevance
“…In basal conditions, the intestinal epithelium is already in a state of physiological hypoxia due to changes in blood flow and tissue oxygenation. This hypoxic state is potentiated in IBD by increased oxygen demand and decreased blood supply . It is shown that HIF1α has an important role in UC.…”
Section: Crosstalk Between Hif and Sepsismentioning
confidence: 99%
“…In basal conditions, the intestinal epithelium is already in a state of physiological hypoxia due to changes in blood flow and tissue oxygenation. This hypoxic state is potentiated in IBD by increased oxygen demand and decreased blood supply . It is shown that HIF1α has an important role in UC.…”
Section: Crosstalk Between Hif and Sepsismentioning
confidence: 99%
“…HIF-1 is believed to control barrier integrity by regulating multiple barrierprotective genes, and its dysregulation may be involved in GI disorders 52,53 .…”
Section: Discussionmentioning
confidence: 99%
“…However, to advance the use of hydroxylase inhibitors for human IBD, potential unwanted adverse side effects of PHIs need to be considered. These include HIF‐mediated induction of erythropoiesis as well as potentially pro‐tumourigenic effects related to HIF activation (Manresa & Taylor, ). A viable strategy to circumvent systemic exposure has been provided by developing a targeted colonic release formulation (Tambuwala et al .…”
Section: Molecular Oxygen Sensing In Metazoan Cellsmentioning
confidence: 99%